Impact of separator's solid‐phase ion conductivity parameter on convection battery performance and modeling. Issue 11 (1st August 2014) - Hilton, Ramsey; Gordon, Michael; Dornbusch, Donald; Suppes, Galen J.
Abstract : A solid‐phase ion conductivity parameter has been added to the separator of a porous electrode theory description of a convection battery performance to increase the accuracy of this model. With the addition of the ion conductivity parameter, the variances between the model and experimental data have been reduced by 80–85% in both the convection cell and the diffusion cell. The parameter is fundamentally consistent with solid‐phase mechanisms by which ions can transport through separators in parallel with liquid‐phase transport, and the improved modeling results substantiate the importance of solid or surface ion transport mechanisms at high current fluxes. Modeling was supplemented with dimensionless analysis to lump fundamental parameters that are inherently coupled in the underlying equations. From this analysis, a global parameter has been developed describing the ratio of convective charge transfer to diffusive charge transfer that characterizes the transition from diffusive to convective cell behavior. © 2014 American Institute of Chemical Engineers AIChE J, 60: 3784–3791, 2014